1997
DOI: 10.1016/s0885-3924(97)00225-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of satisfaction with treatment for chronic pain

Abstract: The purpose of this study was to develop an instrument to assess satisfaction with treatment of chronic pain, evaluate the reliability and validity of this instrument, and then examine predictors and consequences of satisfaction. The Pain Service Satisfaction Test (PSST) is the result of this effort. Fifty adult patients receiving services for chronic pain in a university pain clinic completed the PSST as part of a survey mailed to their homes. Findings supporting the validity of the PSST included significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
72
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 30 publications
7
72
1
1
Order By: Relevance
“…Consistent with our results, several studies have found satisfaction ratings and level of pain to be inversely correlated [44,[46][47]. One study reported that pain severity was unrelated to satisfaction, but outcomes, such as pain relief and improved function after pain treatment, predicted the satisfaction level [48].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with our results, several studies have found satisfaction ratings and level of pain to be inversely correlated [44,[46][47]. One study reported that pain severity was unrelated to satisfaction, but outcomes, such as pain relief and improved function after pain treatment, predicted the satisfaction level [48].…”
Section: Discussionsupporting
confidence: 91%
“…Patient satisfaction ratings have rarely been studied in patients with coexisting depression and pain. McCracken et al examined the combined effect of depression and pain on patient satisfaction and found that depression predicts dissatisfaction with treatment in pain clinic patients [48]. In our study, we found an additive negative effect of both minor and major depression and pain on patient satisfaction.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Also, the interpretation or perception of having control over the pain was related to the satisfaction with pain relief [17]. Some studies showed a significant connection between the treatment satisfaction and the patientprovider relationship [15,18]. The results of the study by Sahlberg-Blom et al from Sweden showed that despite having an assessed lower quality of life in many dimensions than people in general, several patients experienced happiness and satisfaction during their last month of life.…”
Section: Discussionmentioning
confidence: 99%
“…0.97) and ICC (0.67 to 0.81) were obtained in studies proposing the development and validation of instruments for the assessment of patient satisfaction with treatment for chronic and acute pain. 13,14 The KMO criterion used in this adaptation confirmed the one-factor character of the QSP instrument as in the original version of the instrument, which showed 60-81% of the variance. The convergent construct validity of the QSP was confirmed by analysis, and it was in agreement with similar results reported by other authors.…”
Section: Discussionmentioning
confidence: 53%